2018
DOI: 10.3389/fmicb.2018.02602
|View full text |Cite
|
Sign up to set email alerts
|

Novel Self-Transmissible and Broad-Host-Range Plasmids Exogenously Captured From Anaerobic Granules or Cow Manure

Abstract: Novel self-transmissible plasmids were exogenously captured from environmental samples by triparental matings with pBBR1MCS-2 as a mobilizable plasmid and Pseudomonas resinovorans as a recipient. A total of 272 recipients were successfully obtained as plasmid host candidates from granules of an anaerobic methane fermentation plant and from cow manure. The whole nucleotide sequences of six plasmids were determined, including one IncP-1 plasmid (pSN1104-59), four PromA-like plasmids (pSN1104-11, pSN1104-34, pSN0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…These so far cryptic plasmids have no apparent benefit to the host and are still propagated in absence of selective pressure (Fox et al, 2008). A recently discovered group of BHR plasmids are the PromA plasmids, most of which were isolated by exogenous plasmid capture (Schneiker et al, 2001;Tauch et al, 2002;Van der Auwera et al, 2009;Li et al, 2014;Thomas et al, 2017;Yanagiya et al, 2018), hence originated from unknown hosts. Exogenous plasmid isolation allows capturing conjugative as well as mobilizable plasmids from environmental microorganisms by means of biparental and triparental matings without the need to cultivate the host (Smalla et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These so far cryptic plasmids have no apparent benefit to the host and are still propagated in absence of selective pressure (Fox et al, 2008). A recently discovered group of BHR plasmids are the PromA plasmids, most of which were isolated by exogenous plasmid capture (Schneiker et al, 2001;Tauch et al, 2002;Van der Auwera et al, 2009;Li et al, 2014;Thomas et al, 2017;Yanagiya et al, 2018), hence originated from unknown hosts. Exogenous plasmid isolation allows capturing conjugative as well as mobilizable plasmids from environmental microorganisms by means of biparental and triparental matings without the need to cultivate the host (Smalla et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PBS-H4, although this strain lacks the dca cluster genes that are required for complete linuron mineralization (Öztürk et al, 2019). Remarkably, the catabolic PromA plasmids have a near-identical backbone to the previously-described PromA γ plasmids isolated in Japan (Yanagiya et al, 2018). It has been reported before that BHR plasmids isolated from different geographic locations can be highly-conserved (Li et al, 2016; Heuer et al, 2004; Chen et al, 2015b), however, some degree of divergence in the backbone structures of PromA plasmid groups were reported before (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…(Öztürk et al, 2019) (Figure 1). Indeed, RepA-based phylogenetic analysis showed that these plasmids all belong to the PromA γ group, together with the plasmids pSN1104-11 and pSN1104-34 (Yanagiya et al, 2018) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations